Strategi Peningkatan Penerimaan Aplikasi Tracer Study dengan Menggunakan Metode Technology Acceptance Model 2 pada Institut Bisnis Dan Informatika Stikom Surabaya - Trihayuningjati, Bagussukma Kisanggawhisnu; ., Sulistiowati; Kartikasari, Puspita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Stikom Career Center (SCC) Surabaya Stikom is currently using the Tracer Study application to find out how the alumni condition is after 2 years have passed. The Tracer Study application was implemented starting in 2011. The use of the Tracer Study Application to date has not been done at this time.Therefore in this study an analysis of Tracer Study application with the Technology Acceptance Model 2 method consists of Variable Subjective Norms, Images, Job Relevance, Output Quality, Demonstrability Results as independent variables, while the dependent variables include Perceived Usefulness, Perceived Ease of Use, Intention of Use, Use, Behavior and moderating variables of the Experience and Voluntariness variables.From the results of distributing questionnaires as many as 79 respondents and analyzed by Structural Equation Modeling (SEM) method, it was found that Subjective Norm Variables to Image, Perception of Usefulness to Intention of Use, Perception of ease of use towards Perceived Usefulness, Perceived ease of use towards Intention to Use and Intention for Using the Usage Behavior. Based on the results available at this time and the nature of the Stikom Career Center (SCC) in Surabaya, the Stikom must emphasize the ease of use and share access rights.Keywords: Tracer Study, Stikom Career Center (SCC) Surabaya Stikom, Model 2 Acceptance Technology.